Unit 2 Part B
Unit 2 Part B
Unit 2 Part B
Solution:
Step No. Statement Reason
1. ( x )( y ) ( P( x , y )→W ( x , y ) ) Rule P
2. ( y ) ( P(a , y )→W (a , y )) Rule US, 1
3. P(a , b )→W (a , b) Rule US, 2
4. ¬W (a, b) Rule P
5. ¬¿ ¿ P(a,b) Rule T, 3 and 4
11 Show that
(p → q) Λ (r → s), (q → t) Λ (s → u), ~(t Λ u) and (p → r) => ~p.
Step No. Statement Reason
1. (p → q) Λ (r → s) P
2. p→q T, 1
3. r→s T, 1
4. (q → t) Λ (s → u) P
5. q→t T, 4
6. s→u T, 4
7. p→t T, 2, 5
8. r→u T, 3, 6
9. p→r P
10. p→u T, 8, 9
11. ~t → ~p T, 7
12. ~u → ~p T, 10
13. (~t V ~u) → ~p T, 11, 12
14. ~( t Λ u) → ~p T, 13
15. ~(t Λ u) P
16. ~p T, 14, 15
12Show that (a → b) Λ (a → c), ~(b Λ c), (d V a) => d.
Step No. Statement Reason
1. (a → b) Λ (a → c) P
2. a→b T, 1
3. a→c T, 1
4. ~b → ~a T, 2
5. ~c → ~a T, 3
6. ( ~b V ~c ) → ~a T, 4, 5
7. ~( b Λ c) → ~a T
8. ~ (b Λ c) P
9. ~a T, 7, 8
10. dVa P
11. (d V a) Λ ~a T, 9, 10
12. (d Λ ~a) V (a Λ ~a) T, 11
13. (d Λ ~a) V F T, 12
14. d Λ ~a T, 13
15. d T, 14
12. Prove that the premises a → (b → c), d → (b Λ ~c) and (a Λ d) are inconsistent.
Step No. Statement Reason
1. aΛd P
2. a T, 1
3. d T, 1
4. a → ( b → c) P
5. ( b → c) T, 2, 4
6. ~b v c T, 5
7. d → (b Λ ~c) P
8. ~(b Λ ~c) → ~d T, 7
9. ~b V c → ~d T, 8
10. ~d T, 6, 9
11. d Λ ~d T, 3, 10
12. F T, 11
13. Show that the premises “one student in this class knows how to write
programs in JAVA” and “Everyone who knows how to write programs in
JAVA can get a high paying job” imply the conclusion “Someone in this
class can get a high-paying job”.
Let C(x) represent “x is in this class”
J(x) represent “x knows JAVA programming” and
H(x) represent “x can get a high paying job”.
Then the given premises are ∃x (C(x) Λ J(x)) and ∀x (J(x) → H(x)). The conclusion
is ∃x (C(x) Λ H(x)).
Step No Statement Reason
1. ∃x (C(x) Λ J(x)) P
2. C(a) Λ J(a) ES, 1
3. C(a) T, 2
4. J(a) T, 2
5. ∀x (J(x) → H(x)) P
6. J(a) → H(a) US, 5
7. H(a) T, 4, 6
8. C(a) Λ H(a) T, 3 , 7
9. ∃x (C(x) Λ H(x)) EG, 8
14. Show that the conclusion ∀x (P(x) → ~Q(x)) follows from the premises.
∃x (P(x) Λ Q(X)) → ∀y (R(y) → S(y)) and ∃y (R(y) Λ ~S(y))
Step No Statement Reason
1. ∃y (R(y) Λ ~S(y)) P
2. R(a) Λ ~S(a) ES , 1
3. ~(R(a) → S(a)) T, 2
4. ∃y (~(R(y) → S(y)) EG, 3
5. ~∀y(R(y) → S(y)) T, 4
6. ∃x (P(x) Λ Q(x)) → ∀y (R(y) → S(y)) P
7. ~∃x(P(x) Λ Q(x)) T, 5, 6
8. ∀x ~(P(x) Λ Q(x)) T, 7
9. ~ (P(b) Λ Q(b)) US, 8
10. ~P(b) V ~Q(b) T, 9
11. P(b) → ~Q(b) T, 10
12. ∀x (P(x) → ~Q(x)) UG, 11
15. Prove that
x P(x) → x ((P(x) V Q(x)) → R(x)), x P(x), x Q(x) =>
x y (R(x) Λ R(y))
Step No. Statement Reason
1. x P(x) P
2. P(a) ES, 1
3. x Q(x) P
4. Q(b) ES, 3
5. x P(x) → x ((P(x) V Q(x)) → R(x)) P
6. P(a) → ((P(b) V Q(b))R(b)) ES, US, 5
7. (P(b) V Q(b)) → R(b) T, 2, 6
8. P(b) V Q(b) T, 4
9. R(b) T, 7, 8
10. x R(x) EG, 9
11. R(a) ES, 10
12. R(a) Λ R(b) T, 9, 11
13. y (R(a) Λ R(y)) EG, 12
14. x y (R(x) Λ R(y)) EG, 13
16. Use the indirect method to prove that the conclusion z Q(z) follows from
the premises x (P(x) → Q(x)) and y P(y).
Let us assume the additional premise ~(z Q(z)) and prove a contradiction.
Step No. Statement Reason
1. y P(y) P
2. P(a) ES, 1
3. ~(z Q(z)) P
4. z (~Q(z)) T, 3
5. ~ Q(a) US, 4
6. P(a) Λ ~Q(a) T, 2, 5
7. ~(~P(a) V Q(a)) T, 6
8. ~(P(a) → Q(a)) T, 7
9. x (P(x) → Q(x)) P
10. P(a) → Q(a) US, 9
11. (P(a) → Q(a)) Λ ~(P(a) → Q(a)) T, 8, 10
12. F T, 11